METHODOLOGICAL TECHNIQUES TO THE USAGE OF PHRASEOLOGICAL UNITS IN ENGLISH CLASSES - Nasirova R.A. (American Journals Publishing, 2024)
The article explores the significance and challenges of teaching phraseological units in English language classes. It emphasizes the cultural and linguistic value of idiomatic expressions, which not only enrich students' vocabulary but also enhance their linguistic and communicative competencies. The study outlines effective methodological techniques tailored to different educational stages—primary, middle, and high school. These techniques include the use of creative activities, phonetic exercises, and contextual analysis to facilitate understanding, memorization, and application of idioms. Special attention is given to the translation methods of phraseological units, highlighting the importance of preserving their figurative meaning. By integrating phraseological units into the curriculum, the article aims to improve students' pronunciation, grammar, and overall fluency in English, while fostering a deeper appreciation of language and culture.
Keywords: Phraseological units, English language, students, skills.